Komunikator dan Komunikan dalam Pengembangan Organisasi - Sri Wahyuni Harahap; Ruri Regita Br. Ginting; Muhammad Rasyidin; Dedi Sahputra (Universitas Medan Area, 2021)
This article aims to determine the things that need to be considered by communicators and communicants in organizational communication, goals and functions of organizational communication processes, communication as organizational needs and to determine the role of communicators and communicans in organizational development. The problem is focused on how the role of communicators and communicants in organizational life, how communication is needed for organizational development and things that need to be considered by communicators and communicants. In order to approach this problem, theoretical references from various written sources are used. The data were collected through literature study and analyzed qualitatively. This study concludes that communication is the most important part in bridging the interests of individuals and their communities. The communication process will tahe place effectively if communication is carried out in two directions, so that there will be reciprocal interaction between the communicators and communicants in the process of delivering a message, using tools or media that are in accordance with the message conveyed.